Implementasi Metode Hybrid Filtering Technique pada Penentuan Rating Pestisida - Ardimansyah, Ardimansyah; Husain, Husain; Herlinda, Herlinda; Kasmawaru, Kasmawaru; Nurdiansah, Nurdiansah; Marsa, Marsa (Jurnal Teknologi Terpadu, 2024)
Pesticides result from mixing organic chemicals that farmers use to protect their rice plants from disease. Farmers find it difficult to determine pesticide selection due to insufficient information.  So many pesticide products are available on the market, and their various advantages make it increasingly difficult for farmers to choose pesticides suitable for certain rice diseases. This research aims to provide farmers with recommendations on determining the best pesticide to eradicate rice diseases. The wrong choice of pesticide used can harm or reduce farmers' crop yields. This research used the Hybrid Filtering Technique combined with Content Based Filtering and Collaborative Filtering methods to search for weight values ​​and rating prediction values ​​using price criteria, pesticide ingredients, and form (liquid, solid, powder). The results of the calculation analysis of implementing the hybrid filtering technique method for each alternative criterion can simulate a ranking to recommend the best pesticide to eradicate the causes of rice disease. This research has concluded that the rating carried out by farmers who have used pesticides influences the determination of the rating value for each pesticide product. The system test results showed that the type of pesticide with the highest rating value was the enquity pesticide, with a value of 2,256.